Apoptosis-inducing antifungal peptides and proteins. (21st September 2011) - De Brucker, Katrijn; Cammue, Bruno P.A.; Thevissen, Karin
Abstract : Despite the availability of various classes of antimycotics, the treatment of patients with systemic fungal infections is challenging. Therefore the development of new antifungals is urgently required. Promising new antifungal candidates are antimicrobial peptides. In the present review, we provide an overview of antifungal peptides isolated from plants, insects, amphibians and mammals that induce apoptosis. Their antifungal spectrum, mode of action and toxicity are discussed in more detail.